The Effectiveness Of Reading Strategies On Developing Reading Comprehension Among Students In Saudi Arabia - Bashayreh, Lina Abdurrahman Musallam (2018)
The purpose of this study was to investigate the effectiveness of a training program based on metacognitive reading strategies on EFL students’ reading comprehension. To that end and for research data collection purposes, the researcher applied mixed methodology approach. The quantitative research instrumentation consisted of an adapted version of the Metacognitive Awareness of Reading Strategies Inventory (MARSI) that was developed by Mokhtari and Reichard, (2002) and a reading comprehension exam as pre and posttests. The qualitative tool, on the other hand comprised semi- structured interviews that were conducted at the end of the study between the researcher and 10 samples from the experimental group who volunteered to be interviewed. The study sample consisted of 70 EFL students in the Preparatory Year Program (PYP) who were equally distributed over two study groups; (experimental and control) and were purposefully chosen to participate in an intervention that lasted for 8 teaching weeks. Based on the participating students’ pretest results in both quantitative tools, the researcher adapted the current reading curriculum in the ELC and customized it to fit students’ needs for more reading practice and strategy- based instruction towards promoting their reading comprehension. The training program consisted of six selected reading strategies, female- oriented reading passages, and various enriching and engaging activities. After the training has completed and research data were collected and analyzed, the resultant findings showed that there was a significant effect of metacognitive reading strategies on students’ strategy employment and consequently on their reading comprehension. Further, thematic analysis of the interview data revealed an overall satisfaction and positive attitude on the part of the participating students towards the training program, metacognitive reading strategies, and the reading material of training program. The study was concluded by some recommendations for further study and exploration on reading strategies and their relation to reading comprehension, especially in the EFL context.